2018
DOI: 10.1016/j.jfma.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Salivary biomarker combination prediction model for the diagnosis of periodontitis in a Taiwanese population

Abstract: Regarding individual biomarkers, IL-1β, MMP-8, and MMP-9 showed potential for identifying patients with periodontitis. The combination of IL-1β, IL-1ra, and MMP-9 might be feasible for developing a future point-of-care device for diagnosing periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 38 publications
1
51
0
3
Order By: Relevance
“…Different markers may be peaked at different course of disease and when biomarkers of host and microbe origin are combined, the detection of periodontitis maybe improved rather than when used individually [13,30,31], previous studies revealed stronger discriminatory power when IL-1β, MMP-8 and other markers were combined compared with single analysis [32], Pg and MMP-8 in combination [33], ICTP and MMP-8 in combination [34] also exhibited more predictive values. Our data showed that IL-1β individually revealed an AUC value of 0.88 to discriminate periodontitis from healthy subjects, the combination of IL-1β, MMP-8 and Pg strong performance improvement to an AUC value of 0.92, that is consistent with Gursoy's results [35,36], they calculated IL-1β, MMP-8 and Pg together to obtain a cumulative risk score that is highly related with advanced periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different markers may be peaked at different course of disease and when biomarkers of host and microbe origin are combined, the detection of periodontitis maybe improved rather than when used individually [13,30,31], previous studies revealed stronger discriminatory power when IL-1β, MMP-8 and other markers were combined compared with single analysis [32], Pg and MMP-8 in combination [33], ICTP and MMP-8 in combination [34] also exhibited more predictive values. Our data showed that IL-1β individually revealed an AUC value of 0.88 to discriminate periodontitis from healthy subjects, the combination of IL-1β, MMP-8 and Pg strong performance improvement to an AUC value of 0.92, that is consistent with Gursoy's results [35,36], they calculated IL-1β, MMP-8 and Pg together to obtain a cumulative risk score that is highly related with advanced periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results from Mishra et al [11] and Wu et al [13], a minimum of 25 participants per group was set as the sample size of the present study. The SPSS statistical program (Version 21.0; SPSS Inc., Chiacago, IL, USA) was used to analyses the data.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing the literature, we identified research that focused on evaluating whether salivary IL1β levels have the capability to distinguish between patients with different periodontal conditions (Afacan et al, 2018; Ebersole et al, 2013, 2015; Isaza‐Guzmán et al, 2017; Ramseier et al, 2009; Sánchez et al, 2013; Wu et al, 2018). After analysing these studies in‐depth, we verified the heterogeneity with respect to methodological factors that may affect the diagnostic classification parameters associated with a biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…However, until now, compliance with this characteristic has been almost impossible when evaluating salivary biomarkers for the diagnosis of periodontitis (Arias‐Bujanda et al, 2020). In the case of IL1β, the described sensitivity values ranged from 88% to 54% and specificity from 100% to 52% (Afacan et al, 2018; Ebersole et al, 2013, 2015; Isaza‐Guzmán et al, 2017; Ramseier et al, 2009; Sánchez et al, 2013; Wu et al, 2018). This discrepancy may be due to the differences observed between the studies in relation to the different control groups and the different groups of periodontal patients analysed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation